Structural modifications on passive cooling tiles - Tripathi, Kartikeya (Nanyang Technological University, 2024)
Considering the rising global temperatures, it is becoming increasingly relevant to find sustainable solutions that help alleviate the exacerbated effects of climate change. The reliance on appliances like Heating, Ventilation, and Air Conditioning (HVAC) systems intensifies this vicious cycle of environmental degradation and necessitates alternative cooling methods. This research explores the development of a new concrete mixture, that maximizes porosity for concrete tiles, to leverage passive cooling techniques, particularly evaporative cooling, and acts as an alternative to traditional cooling methods. Conventional solutions to using concrete for passive cooling involved implementing external attachments, like reflectors and sheet coatings, or merely varying the geometry of concrete structures. However, these have been proven to be costly, and ineffective, when considering the context of tropical climates like Singapore, which have high humidity and solar irradiance. Hence, this study aims to address such limitations by modifying the very concrete mixtures used and by incorporating passive cooling directly into them. To create concrete tiles with a new composition in the mixture, this research varies the key ingredient proportions in the form of the water-to-cement (W/C) ratio and incorporates a Supplementary Cementitious Material: Ground Granulated Blast Furnace Slag (GGBS). An iterative process of varying these different parameters was followed, so as to find the optimum composition that maximizes porosity, water absorption, and cooling capabilities, while maintaining mechanical strength. Various samples were fabricated and tested under standard conditions by quantitatively measuring their Water Absorption %, Maximum Compressive Stress (MPa), and Temperature variations. The findings indicate the feasibility of creating concrete tiles that meet the requirements for porosity, water absorption, and strength, as well as the general trend for how these parameters might vary with different compositions of W/C Ratio and GGBS%. Overall, this research contributes to the development of sustainable cooling solutions and highlights the importance of incorporating concepts like Passive cooling into everyday life through the construction industry. The paper provides a base and framework for future research into optimizing W/C ratios, porosity, and mechanical strength such that cooling can be achieved. Additionally, the study also highlights the potential for future exploration, including long-term performance studies, integration with building designs, and incorporation of other sustainable cooling elements.